2014
DOI: 10.1155/2014/502123
|View full text |Cite
|
Sign up to set email alerts
|

The Physiological and Biochemical Outcomes Associated with a Reflexology Treatment: A Systematic Review

Abstract: Background. Reflexology is one of the top forms of complementary and alternative medicine in the UK and is used for healthcare by a diverse range of people. However, it is offered by few healthcare providers as little scientific evidence is available explaining how it works or any health benefits it may confer. The aim of this review was to assess the current evidence available from reflexology randomised controlled trials (RCTs) that have investigated changes in physiological or biochemical outcomes. Methods.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 36 publications
2
35
0
1
Order By: Relevance
“…Like Fs, Rf has a status of evidence in stress management, shown to be useful for relaxation, stress reduction, or anxiety relief. (17) The level of evidence results in methodologic (18) and basic research, (19) and in both qualitative (20,21) and quantitative clinical trials. But the latter, contributing to the edification of arguments, focused interest on stress and anxiety in seriously ill people.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Like Fs, Rf has a status of evidence in stress management, shown to be useful for relaxation, stress reduction, or anxiety relief. (17) The level of evidence results in methodologic (18) and basic research, (19) and in both qualitative (20,21) and quantitative clinical trials. But the latter, contributing to the edification of arguments, focused interest on stress and anxiety in seriously ill people.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…That finding provides some support for a published review 4 of RCTs that had a narrow clinical focus (setting) in which reflexology was found to significantly affect fatigue, sleep, and pain outcomes, and also published evidence for an acute reduction of perceived psychological stress following reflexology that is reproducible with repeat treatments. 21 There is also some literature evidence 21,22 for effect of reflexology on systolic/diastolic blood pressure and heart rate when this is specifically related to the stress response, but in this review no evidence was found to associate biometric responses with any particular measure. Present and related findings therefore support expressed views 1,2,3,5 that less heterogeneity of pathologies and study objectives would aid interpretation of clinical outcomes of reflexology.…”
Section: Discussionmentioning
confidence: 78%
“…For a future trial, the use of sham reflexology may be a more appropriate sham treatment, as it may be easier to blind participants and attrition rates in reflexology studies employing sham reflexology have been acceptable [28]. However, a recent reflexology review highlights that finding an appropriate sham treatment for reflexology without stimulating the feet reflexes may be challenging as even light pressure on the feet may stimulate the reflexes [29]. Several studies using sham reflexology as a comparator for true reflexology found positive effects of both treatments, or smaller differences between groups [24,28], supporting the theory that it is difficult to work with the feet without stimulating the reflexes.…”
Section: Discussionmentioning
confidence: 99%